Solidarity cities confronting racial capitalism, mapping transformation - Safri, Maliha 1975-; Pavlovskaya, Marianna 1963-; Healy, Stephen 1972-; Borowiak, Craig Thomas 1971- (University of Minnesota Press, 2024)
"Solidarity Cities analyzes the deeply entrenched racial and economic divides from which cooperative networks emerge as they work to provide unmet basic needs. The authors show how these initiatives act as bulwarks against gentrification, exploitation, and economic exclusion, helping readers see them as part of the past, present, and future of more livable and just cities."
Keywords: Rassismus; Solidarische Ökonomie; Stadtentwicklung; Kooperation; Soziale Ungleichheit; Kapitalismus; USA; Community development, Urban / United States / Case studies; Cooperation / United States / Case studies; City planning / Social aspects / United States; Social justice / United States / Case studies; Développement communautaire urbain / États-Unis / Études de cas; Justice sociale / États-Unis / Études de cas